The Influence of the Learning Cycle Learning Model on Students’ Creative Thinking Skills in Science Learning - Prebiyanto, Bambang; Budiastra, A. A. Ketut; Rosita, Tita (Advances in Social Sciences Research Journal, 2024)
The issue of creative thinking skills in elementary school students is very basic because to achieve learning success in science learning at the elementary school level, it is necessary to increase creative thinking skills in elementary school students. The purpose of this study is to determine the development of the Learning Cycle learning model to improve the creative thinking ability of elementary school students in science learning. This research is an experimental study, which looks at the causal relationship. There were two groups of classes compared in this study, namely the control class and the experiment. Data collection is quantitative data obtained from pretest and posttest results in control classes and experiments. Then to see the improvement of students’ abilities from the initial test to the final test using normal Gain scores. The results of the analysis can be concluded that learning with the Learning Cycle model can improve the creative thinking ability of grade IV elementary school students in science learning. In addition, conventional learning can also improve the creative thinking ability of grade IV elementary school students in science learning. However, based on quantitative data collection obtained from pretest and posttest results in control classes and experiments, there are very significant differences in the increase in creative thinking skills of grade IV elementary school students in science learning.